Spark plasma sintering of dielectric BaTaO2N close to the melting point of the BaCN2 additive. Issue 6 (June 2020) - Hosono, Akira; Inoguchi, Masashi; Masubuchi, Yuji; Murayama, Koji; Iha, Michiaki; Higuchi, Mikio; Kikkawa, Shinichi
Abstract: The perovskite-type oxynitride BaTaO2 N is a promising lead-free relaxor ferroelectric material. However, this material releases a part of its nitrogen during its sintering above 1350 °C. Subsequent annealing of the resulting sintered BaTaO2 N0.85 ceramics under an ammonia flow is necessary to recover an insulating, stoichiometric BaTaO2 N ceramics. Very recently, molten BaCN2 was reported to be a useful flux for the preparation of BaTaO2 N microcrystals without the loss of nitrogen. In the present work, BaTaO2 N powder was sintered with a BaCN2 additive under mechanical pressure, using a spark plasma sintering system. Nitrogen loss from the BaTaO2 N ceramic was avoided during liquid phase sintering at approximately 900 °C. The stoichiometric BaTaO2 N ceramic product with a relative density of 79.8 % was an electrically insulator and it showed its relative dielectric constants, εr, in the range from 320 to 650 and a loss tan δ values from 0.04 to 0.19 at room temperature.